Efficient synthesis of trefoil-shaped tricyclic polymers by a ROMP-based blocking-cyclization technique - Wang, Hao; Ma, Cuihong; Han, Zhiying; Liao, Xiaojuan; Sun, Ruyi; Xie, Meiran (Polymer chemistry, 2024)
Cyclic polymers have unique physical properties and attract extensive attention, but the precision synthesis of complex cyclic polymers is a challenging subject. Herein, by using a polymeric ladderphane with six living ends as the initial motif, complex trefoil-shaped tricyclic polymers were precisely synthesized by a ring-opening metathesis polymerization-based blocking-cyclization technique in a simplified process, where three macromolecular rings consisting of multiple repeating units were covalently interconnected at a single junction point, and the ring size was readily regulated by varying the feed ratio of monomers. The topological structures and physical properties of trefoil-shaped tricyclic polymers were fully characterized. Importantly, the molecular topology of trefoil-shaped tricyclic polymers was clearly observed. Therefore, this work provides an effective strategy for the synthesis of complex cyclic polymers. Complex trefoil-shaped tricyclic polymers with regulated ring sizes were precisely synthesized by a ROMP-based blocking-cyclization technique, their structures were characterized, and their cyclic macromolecular topology was clearly observed.